A1 bounds for Calderón-Zygmund operators related to a problem of Muckenhoupt and Wheeden - Lerner, Andrei K. (2009)
We obtain an Lp(ω) bound for Calderón-Zygmund operators T when w∈ A1. This bound is sharp both with respect to ||ω||A1 and with respect to p. As a result, we get a new L1,∞°(ω) estimate for T related to a problem of Muckenhoupt and Wheeden.